Collecting to preserve the memory of urban transport. A collective adventure - Jarrigeon, Anne; Chervin, Jacqueline; Lefrançois, Dominique (Hamburger Journal für Kulturanthropologie (HJK), 2015)
Since 1957 members of one association (Association d’amateurs de transports urbains et interurbains) have collected old buses, tramways, subways, maps, tickets, films, pictures, trips … There impressive collection should now take place in the future Urban Transport Museum near Paris. This project was an occasion to realise an oral and audiovisual archive campaign, in which we used to take part. We present here this research on those lovers of public transport and their collective commitment to the preservation of this patrimony.